Social networks in venezuelan community social management - Maestre, José Gregorio Lemus; Suniaga, Felicita Lemus de; Roque, Nancy Pérez de (Revista Hipótese, 2020)
From the objective of analyzing community management through the use of social networks for social mobilization, the qualitative documentary methodology was used with the analysis of discourse, which allowed us to review community practices with the use of social networks in the Venezuelan territory, with attention to the social movement that develops in the Urb "Santa Catalina", in the city of Cumaná; from the results found, civic orientations are established where a necessary review and re-direction of the community movement is proposed with media, horizontal actions to seek in an unfinished way better living conditions.
Keywords: Community social management; Social networks; Social transformation; Good living; Communication